Tantangan Teologi Agama-agama: Suatu Diskursus Model - Hasahatan Hutahaean (KURIOS (Jurnal Teologi dan Pendidikan Agama Kristen), 2020)
Live side by side between religions is no longer a choice of life, especially in Indonesia. Because Indonesian society is formed from various religions and tribes or sub-tribes. Therefore, the effort to find a format and order to live side by side in getting along well and harmony is a relevant topic of all time. In this paper, the pattern of life in diversity is traced to the time of the first human life on earth through the narrative of the Scriptures in Christianity, the Bible. With the help of searching for cognate libraries, this paper presents proposals that are simple and easy to understand for each adherent of the religion. Various data collected were then processed using the heuristic inquiry theory approach while the data from the scriptures were explored with a hermeneutic pattern. The tripolar typology that is considered to be the first or pioneering pattern in the theology of religions is now gaining a new partner in realizing life between religious communities towards harmony. Abstrak Hidup berdampingan antar pemeluk agama tidak lagi menjadi pilihan hidup, apalagi di Indonesia. Sebab masyarakat Indonesia terbentuk dari berbagai agama dan suku atau sub-suku. Karena itu pula upaya mencari format dan tatanan hidup berdampingan dengan rukun dan harmonis menjadi topik yang relevan sepanjang masa. Dalam tulisan ini, pola kehidupan dalam keberagaman ditelusuri hingga masa-masa kehidapan pertama manusia di bumi melalui narasi Kitab Suci dalam kekristenan yaitu Alkitab. Dengan bantuan penelusuran pustaka serumpun, tulisan ini menyajikan usulan yang sederhana dan mudah untuk dimengerti oleh masing-masing pemeluk agama. Berbagai data yang berhasil dihimpun kemudian diolah dengan pendekatan teori heuristic inquiry sedangkan data dari kitab suci didalami dengan pola hermeneutik. Kerangkeng tipologi tripolar yang dianggap menjadi pola pertama atau perintis dalam teologi agama-agama kini memperoleh mitra baru dalam mewujudkan kehidupan antar umat beragama menuju keharmonisan